Features of radiological and anatomical changes in bone of the hip joint due to injuries - Filipenko, Volodymyr; Zlatnyk, Ruslan; Bondarenko, Stanislav; Akonjom, Mandus (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To conduct a retrospective analysis of radiographs and CT scans for studying of typical changes in acetabulum (A) and proximal femur (F) in patients with the consequences of injuries in the area of the hip joint. Methods: We analyzed radiographs and CT scans in 106 patients. Patients were divided into groups: I — false joint of F neck, II – false joint at the level of per-, inter- and subtrochanteric area of F, III — post-traumatic avascular necrosis of F head, IV — posttraumatic coxarthrosis, V — inveterate fracture dislocation. We performed an assessment of condition of the joint space and endplates, F head shape, peculiarities of A, continuity of the pelvic ring, condition of the neck and the proximal F, gap width in pseudarthrosis, defects of greater and lesser thochanters, migration of proximal F up, the presence of metal construction (MK), its stability, and resorption of bone tissue around it. Status of bone structures we evaluated according to Singh and Barnett-Nordin indices. Results: There were determined distinctive changes in the hip joint in each group: I — lysis of the F neck (dominated by full one in 38 % patients), displacement of the proximal F (67 %), MK (40 %), its migration into the joint cavity (14 %), perforation of the A walls (12 %), and osteoporosis (91 %); II — lysis of the F neck in 43 % patients (in 29 % complete one), defects in greater (71 %) and lesser (86 %) trochanters, dislocation of the proximal F and osteoporosis in 100 %, MK (29 %); III — deformation of the F neck (100 %), defects of the A walls (36 %), displacement of the proximal F (82 %), MK (36 %) and osteoporosis (100 %); IV — deformation of the A wall with its defects (80 %), displacement of the proximal F (86 %), MK (31 %) and osteoporosis (91 %); V — defects of the A wall (100 %), violation of pelvic ring integrity (70 %), displacement of the proximal F (40 %), stable MC (20 %), and osteoporosis (100 %). Conclusion: Considering results obtained after arthroplasty in patients with sequelae of injuries in the hip joint it is possible to optimize preoperative planning and to improve treatment.